Light assisted rechargeable batteries: a proof of concept with BODIPY derivatives acting as a combined photosensitizer and electrical storage unit. Issue 5 (12th January 2017) - Godet-Bar, T.; Leprêtre, J.-C.; Poizot, P.; Massuyeau, F.; Faulques, E.; Christen, A.; Minassian, F.; Poisson, J.-F.; Loiseau, F.; Lafolet, F.
Abstract : Photosensitive dye based boron dipyrromethene polymer has been investigated in the scope of photo-assisted rechargeable batteries. Abstract : Photosensitive dye based boron dipyrromethene polymer has been investigated in the scope of photo-assisted rechargeable batteries. Under visible light, a 0.8 V gain has been observed for the BODIPY moiety reduction process. The light energy contributes advantageously to the charge yield of the organic material potentially involved in lithium batteries.